A new transportable floating mesocosm platform with autonomous sensors for real‐time data acquisition and transmission for studying the pelagic food web functioning. (23rd July 2013) - Mostajir, Behzad; Le Floc'h, Emilie; Mas, Sébastien; Pete, Romain; Parin, David; Nouguier, Jean; Fouilland, Eric; Vidussi, Francesca
<x xml:space="preserve">Abstract</x> We describe a new transportable floating mesocosm platform with autonomous sensors. The platform has 9 separate units that can be transported by medium‐sized research vessels and positioned in coastal waters. The in situ mesocosms are equipped with a set of sensors for measuring water temperature, conductivity, chlorophyll a fluorescence (Chl a), and dissolved oxygen concentration. It can take measurements every 2 min, store these measurements, and transmit them in real time. Each mesocosm has a pump with regulated flow to mix the water column. One of the floating units is used as an in situ observatory to monitor the water temperature and Chl a in the water around the mesocosms as well as weather data and the incident light. The main data logger on the platform sends all the data collected to a remote PC computer. This floating mesocosm platform was successfully deployed in 2010 and 2011 in Mediterranean coastal waters (Thau lagoon and Cretan Sea, respectively). Simultaneous, automatic, high temporal resolution monitoring of physical, chemical, and biological parameters in the mesocosms proved to be a powerful, noninvasive, and effective approach for i) monitoring the variations in physical and chemical parameters in real time and ii) assessing the short‐term variations in Chl a and the pelagic food web metabolism (e.g., the community respiration, gross primary production, and net community production) in the mesocosms without any manipulation of water samples.